The Influence Of E-Filing Implementation On Taxpayer Compliance Through Service Quality Satisfaction At Kpp Pratama Sidoarjo Barat - Wulansari, Yuli Yanti; Hapsari, Munawaroh (Universitas 17 Agustus 1945 Surabaya, 2025)
The purpose of this study is to examine the impact of e-filing implementation on taxpayer compliance through service quality satisfaction at KPP Pratama Sidoarjo Barat. This research employs a quantitative approach with a survey method, using a sample of 100 taxpayers registered at KPP Pratama Sidoarjo Barat. Data analysis is conducted using the Partial Least Squares (PLS) technique through the SmartPLS 4 application. The data testing techniques applied in this study include validity tests, reliability tests, discriminant validity tests, Fornell-Larcker tests, cross-loading tests, R-square tests, and t-tests. The findings indicate that the implementation of e-filing has a positive and significant effect on taxpayer compliance through service quality satisfaction, with a significance value of 0.000 < 0.005. Indirect analysis results reveal that e-filing implementation (X), mediated by service quality satisfaction (Z), significantly influences taxpayer compliance (Y). These results highlight the crucial role of service quality satisfaction in strengthening the relationship between e-filing implementation and taxpayer compliance. This study provides insights for tax authorities to enhance digital tax services by improving e-filing usability, accessibility, and service quality. By optimizing these factors, tax authorities can increase taxpayer satisfaction and, consequently, improve voluntary tax compliance.